Partial Purine Nucleoside Phosphorylase Deficiency Helps Determine Minimal Activity Required for Immune and Neurological Development - Grunebaum, Eyal; Campbell, Nicholas; Leon-Ponte, Matilde; Xu, Xiaobai; Chapdelaine, Hugo (Frontiers in Immunology, 2020)
Introduction: Complete or near complete absence of the purine nucleoside phosphorylase (PNP) enzyme causes a profound T cell immunodeficiency and neurological abnormalities that are often lethal in infancy and early childhood. We hypothesized that patients with partial PNP deficiency, characterized by a late and mild phenotype due to residual PNP enzyme, would provide important information about the minimal PNP activity needed for normal development. Methods: Three siblings with a homozygous PNP gene mutation (c.769C>G, p.His257Asp) resulting in partial PNP deficiency were investigated. PNP activity was semi-quantitively assayed by the conversion of [14C]inosine in hemolysates, mononuclear cells, and lymphoblastoid B cells. PNP protein expression was determined by Western Blotting in lymphoblastoid B cells. DNA repair was quantified by measuring viability of lymphoblastoid B cells following ionizing irradiation. Results: A 21-year-old female was referred for recurrent sino-pulmonary infections while her older male siblings, aged 25- and 28- years, did not suffer from significant infections. Two of the siblings had moderately reduced numbers of T, B, and NK cells, while the other had near normal lymphocyte subset numbers. T cell proliferations were normal in the two siblings tested. Hypogammaglobulinemia was noted in two siblings, including one that required immunoglobulin replacement. All siblings had typical (normal) neurological development. PNP activity in various cells from two patients were 8–11% of the normal level. All siblings had normal blood uric acid and increased PNP substrates in the urine. PNP protein expression in cells from the two patients examined was similar to that observed in cells from healthy controls. The survival of lymphoblastoid B cells from 2 partial PNP-deficient patients after irradiation was similar to that of PNP-proficient cells and markedly higher than the survival of cells from a patient with absent PNP activity or a patient with ataxia telangiectasia. Conclusions: Patients with partial PNP deficiency can present in the third decade of life with mild-moderate immune abnormalities and typical development. Near-normal immunity might be achieved with relatively low PNP activity.